Chapter Patient-generated evidence in Epidermolysis Bullosa (EB): Development of a questionnaire to assess the Quality of Life - Pilo, Cinzia (Proceedings e report, 2021)
Epidermolysis Bullosa (EB) is a group of genetic conditions that cause fragile and blistering skin. Although there are different types of EB, which differ in severity, their signs and symptoms overlap. As a result of this disorder, patients face an unbearable burden in their lives, and their Quality of Life (QoL) is negatively affected at every life cycle stage. Nevertheless, the assessment of the quality of life of these patients is scanty. This project aims to develop a patient-centered questionnaire to assess the QoL of EB patients. This tool will be a valid aid for clinicians to understand patients better and identify the areas that need more attention; moreover, it will allow them to follow the patients over time and evaluate the impact of any treatments. The methodological process to develop the questionnaire consisted of two phases: firstly, a critical review of scientific literature was performed; secondly, a pseudo-Delphi study was carried out. A multidisciplinary panel (including patients, caregivers, and clinicians) actively participated in round tables to discuss the main areas of interest. Starting from this initial set of areas and through the repetition of Delphi (up to three rounds), a gradual refinement of the statements was carried out to define a list of items to be included in an easy-to-use but meaningful questionnaire. The final patient-centered questionnaire is thus able to measure the QoL beyond the physical symptoms and the clinical evolution of the disease, encompassing functional autonomy, psycho-emotional state, social relations and the working field.